2022
DOI: 10.1039/d2ob01524b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in photochemical construction of aromatic C–P bonds via C–hetero bond cleavage

Abstract: Photochemical C–P bond cross-coupling in aromatics via C–X (X = F, Cl, Br, I), C–N bond and C–O bond cleavages with/without photosensitizer were summarized in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…In this eld, photo-, 5 metallaphotoredox 6 and electron-donor-acceptor (EDA) methods 7 (Scheme 1A) have been employed using different aryl radical precursors, such as aryl halides, aminated arenes, or aryl sulfonates through homolytic cleavage of C(sp 2 )heteroatom bonds. 8 In addition, two examples of light induced direct C(sp 2 )-H phosphonation have been reported in the same year. One of them, developed by König functionalizes electronrich arenes by means of a ruthenium photocatalyst in combination with ammonium persulfate as sacricial oxidant, 9 while the second reported by Lei group uses a dual catalytic system composed of acridinium photosensitiser and a Co co-catalyst.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In this eld, photo-, 5 metallaphotoredox 6 and electron-donor-acceptor (EDA) methods 7 (Scheme 1A) have been employed using different aryl radical precursors, such as aryl halides, aminated arenes, or aryl sulfonates through homolytic cleavage of C(sp 2 )heteroatom bonds. 8 In addition, two examples of light induced direct C(sp 2 )-H phosphonation have been reported in the same year. One of them, developed by König functionalizes electronrich arenes by means of a ruthenium photocatalyst in combination with ammonium persulfate as sacricial oxidant, 9 while the second reported by Lei group uses a dual catalytic system composed of acridinium photosensitiser and a Co co-catalyst.…”
mentioning
confidence: 94%
“…A range of 2-substituted anisoles were amenable to this transformation, obtaining 2-nitrile (4), 2-halogenated (5 and 6) and 2-aldehyde (7) derivatives in high yields. Arenes containing alkylated substitutions were also competent substrates (8)(9)(10), yielding the desired aryl phosphonates from moderate to good yields. Biphenyls were used as coupling partners with success including biphenyl (11) and 4-bromophenyl (12), which the presence of the bromide allows subsequent postfunctionalization.…”
mentioning
confidence: 99%
“…13,[17][18][19][20][21][22] With the aid of microwave apparatus, Keglevich et al reported catalyst-free, 23 ligand-free 24 and ligand-free/ solvent-free 25,26 conditions for coupling C SP 2-P(vO) bonds. In addition to a recently developed photocatalyst-free (transitionmetal-free) method for making valuable organophosphorus compounds, 27 importantly, Montchamp et al demonstrated that the C SP 2-P(vO) coupling of 2-chloropyrazine was successfully catalysed by 1 mol% of an in situ Pd(OAc) 2 /dppf catalytic system. 28 It is also noteworthy that Herzon and co-workers showed that the coupling of secondary phosphine oxides (SPOs) and aryl iodides could be catalysed at room temperature by Pd 2 dba 3 /Xantphos (0.5 mol%/1 mol%).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, radical phosphorylation has emerged as a powerful platform for the construction of tertiary phosphines (Scheme b). The first radical phosphorylation of organic halides and alkyl imidazole-1-carbothioate with chlorodiphenylphosphine has been exploited by Oshima and Yorimitsu et al in boiling benzene . By employing Me 3 SnPPh 2 as a P-source, Studer and Curran et al.…”
mentioning
confidence: 99%